KEMAMPUAN PERTUMBUHAN EKONOMI MEMODERASI PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAU DAN DBH PADA BELANJA MODAL - Bagus Indra Mulia Nugraha, I Putu; Dwirandra, A.A.N.B (E-Jurnal Akuntansi, 2016)
Independent variables such as local taxes, levies, DAU, DBH, and economic growth is presumed not always linear effect on capital expenditures, due to contingent factors that influence the relationship. One such contingency factor is economic growth. This research aims to know the ability of economic growth moderating influence of local taxes, levies, DAU and DBH in capital expenditure. The research covers eight counties and one city in the province of Bali in the span of observations from 2009 to 2013. Sampling method used in this study is saturated sample. The results show that local taxes, levies, DAU and economic growth positive effect on capital spending while DBH no effect on capital spending. Economic growth is able to moderate the effect of local taxes and levies on capital expenditure, but not able to moderate the influence of DAU and DBH in capital expenditure.
Keywords: Local Taxes, Levies, DAU, DBH, Economic Growth, Capital Expenditure